Re-evaluating ‘Silkworm’ Cocoons in Early Medieval Poznań: A Critical Analysis - Aldona Kurzawska; Olga Antowska-Gorączniak; Edward Baraniak (Slavia Antiqua)
We provide a comprehensive re-examination of the early medieval cocoons unearthed during archaeological excavations in the Cathedral Square at Ostrów Tumski, Poznań, Poland, in the 1950s. We challenge previous identifications, in particular the misidentification of these cocoons as Bombyx mori (silk moth) which influenced the interpretation of sericulture practices in the region. Comprehensive comparative microstructural analyses, including digital microscopy and scanning electron microscopy, as well as the association of the cocoons with structures, validate our revised identification as Hymenoptera (possibly parasitic wasp) cocoons. While silkworm breeding and silk production did not occur in 11th-century Poznań, our meticulous review of the historical records highlights the appearance of silk fabric as early as the 9th and 10th centuries in Poland trough trade routes likely originating in China and Byzantium. We underline the significance of Hymenoptera cocoons, a rarity in archaeology. In addition to contributing to a more accurate understanding of the history of silk textiles in early medieval Poland, and enriching knowledge of global trade contacts and cultural connections, our study emphasizes the importance of challenging and updating scholarly findings as the research methods improve.